The governance of landscape management: new approaches to urban open space development. (17th November 2019) - Jansson, Märit; Vogel, Nina; Fors, Hanna; Randrup, Thomas B.
ABSTRACT: The concept and practice of urban open space (UOS) management is becoming increasingly influenced by varying governance arrangements for participatory co-development. These varying arrangements generate multifaceted approaches to UOS management as well as to landscape architecture more broadly. Governance and management constitute two central themes within UOS development, but their combination has so far been little addressed, despite its potential in addressing different desired values and processes. This paper uses a secondary case study approach to highlight and analyse this combination in different contexts and discusses conceptual use and knowledge gaps within landscape architecture, critically rethinking current process logics, reflecting on new tendencies for co- and self-management and discussing consequences for theory and practice. The conceptual understanding of governance approaches in UOS management presented may be useful for sustainable long-term development of UOS.